Diagnostic and prognostic value of O-linked N-acetylglucosamine transferase transferase in bladder neoplastic transformation in postmenopausal women - Krześlak, Anna; Wikosz, Jacek; Forma, Ewa; Różański, Waldemar; Bryś, Magdalena; Blewniewski, Mariusz; Lipiński, Marek (Menopause Review/Przegląd Menopauzalny, 2011)
Aim of the study : The aim of the study was to evaluate the usefulness of mRNA expression of O-GlcNAc transferase (OGT) for bladder neoplasm diagnosis and disease prognosis in postmenopausal women. Material and methods : OGT expression was measured by a real-time PCR assay in urine obtained from 52 postmenopausal women with bladder neoplasms and 37 healthy women. For the studied gene, cut-off, specificity and sensitivity were estimated. Results: For OGT, the cut-off value was 416.93, sensitivity 100% and specificity 88.9%. Expression of OGT was established in 36/46 (78.2%) urine specimens taken from women with bladder cancer and in 18/37 (48.6%) urine specimens from healthy women. There was no OGT expression in women with papillary urothelial neoplasms of low malignant potential (PUNLMP). Conclusions : Measurement of OGT mRNA level in urine samples obtained from postmenopausal women with urinary bladder cancer may be a useful marker of diagnosis and prognosis.